Implementasi ketentuan iddah dan ihdad dalam KHI: Tantangan penerapan di pengadilan agama era modern - Arifin, Ihsan Al; Israqunnajah, Israqunnajah (Maliki Interdisciplinary Journal, 2025)
This article analyzes the implementation of the provisions on iddah and ihdad in the Compilation of Islamic Law (KHI) and examines the challenges faced by Religious Courts in the modern era. The study is motivated by the increasing dynamics of divorce cases and the low level of public literacy regarding the calculation of the waiting period, which often leads to misinterpretations of iddah, legal uncertainty, and disparities in practice across regions. An analytical-critical approach is employed to evaluate the quality, relevance, and validity of KHI’s provisions by correlating classical fiqh theory, empirical data, and judicial practices. The findings reveal that although KHI holds formal legitimacy, it has not yet accommodated contemporary complexities, particularly issues involving working women, reproductive technologies, and local cultural variations in observing ihdad. The lack of detailed technical regulations compels judges to refer back to classical fiqh, which is not always contextually relevant, resulting in inconsistencies in judicial decisions. This article emphasizes the need for interpretive reform based on maqāṣid al-sharī‘ah and strengthened public legal education so that the implementation of iddah and ihdad becomes more adaptive, equitable, and aligned with the needs of Muslim communities in Indonesia.